2016
DOI: 10.1016/j.ijid.2016.02.1006
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of brucella spp in aborted bovine fetuses by real-time PCR

Abstract: Background: Brucellosis is a highly contagious zoonotic disease that has serious implications on human and animal health. In animals, brucellosis affects reproduction, causing abortion mainly in cows. The aim of this study was to determine the prevalence of brucellosis in different tissues of the bovine fetuses and to analyze whether the amount of the DNA detected changes after formaldehyde treatment and putrefication.Methods & Materials: The material studied was composed of 70 aborted cattle fetuses brought t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Previous studies conducted in Turkey revealed that detection rate of Brucella spp. in bovine foetuses varies between 14.3% (10/70) and 41.2% (40/97) (Aslan, Yoldas, Yigin, Demirci, & Saglam, 2016; Buyuk & Sahin, 2011), whereas in sheep foetuses ranges from 18.7% (12/64) to 53.4% (31/58) (Erganis, Kaya, Hadimli, & Guler, 2002; Ica et al., 2012). Furthermore, studies on the prevalence of Campylobacter spp.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies conducted in Turkey revealed that detection rate of Brucella spp. in bovine foetuses varies between 14.3% (10/70) and 41.2% (40/97) (Aslan, Yoldas, Yigin, Demirci, & Saglam, 2016; Buyuk & Sahin, 2011), whereas in sheep foetuses ranges from 18.7% (12/64) to 53.4% (31/58) (Erganis, Kaya, Hadimli, & Guler, 2002; Ica et al., 2012). Furthermore, studies on the prevalence of Campylobacter spp.…”
Section: Discussionmentioning
confidence: 99%